High-rate formation cycle of Co3O4 nanoparticle for superior electrochemical performance in lithium-ion batteries. (1st February 2019) - Cheong, Jun Young; Chang, Joon Ha; Cho, Su-Ho; Jung, Ji-Won; Kim, Chanhoon; Dae, Kyun Seong; Yuk, Jong Min; Kim, Il-Doo
Abstract: Formation cycle is a significant step in battery processing, as it leads to the build-up of stable solid electrolyte interphase layer that affects various parameters of batteries. Although fast formation cycle is more economical way to realize the battery production, it is generally known that fast formation cycle of conventional electrode materials leads to capacity degradation. In this study, we report the high-rate formation cycle step to induce excellent electrochemical performance, in the case of Co3 O4 nanoparticle. Surprisingly, Co3 O4 nanoparticle that runs in the formation cycle at rather high current density (1.0 A g −1 ) exhibits superior electrochemical performance compared with Co3 O4 nanoparticle that runs in the formation cycle at 0.05 A g −1 . Such enhanced electrochemical performance after the high-rate formation cycle for Co3 O4 can be mainly attributed to the stabilization of solid electrolyte interphase layer upon cycling and initial partial agglomeration that forms secondary particles. This work firstly paves the possibility of employing high-rate formation cycle to induce improved electrochemical performance, which can also be extended to various alternative electrode materials. Graphical abstract: Image 1 Highlights: Detailed in-depth study on the effect of high-rate formation cycle. The effect of formation cycle was investigated for Co3 O4 . High-rate formation cycle leads to enhanced electrochemical performance. Both interfacial and morphological transitions depend on formation cycle.